The Effect Of Net Profit Margin, Sales Growth, And Profitability On The Dividend Pay-Out Ratio With Managerial Ownership As A Moderation - Khansa Mara Kartika; Zulfikar (E-Jurnal Akuntansi, 2025)
This study analyzes the effect of Net Profit Margin, Sales Growth, and Profitability on the Dividend Payout Ratio in manufacturing companies in the primary consumer goods and industrial sectors in Indonesia for the period 2021–2023, with Managerial Ownership as a moderating variable. Secondary data were obtained from company reports, previous research, the IDX, and official websites, using a purposive sampling method. The analysis used multiple linear regression and Moderated Regression Analysis (MRA) using SPSS, and classical assumptions were tested to ensure model validity. The results show that Sales Growth and Profitability have a significant positive effect on the Dividend Payout Ratio, while Net Profit Margin has no significant effect. Managerial Ownership also does not moderate the relationship between the independent variables and the Dividend Payout Ratio. The study's limitations include a limited sector and a three-year period post-pandemic.